America Imagined - Körner, Axel. author. aut Link
IX, 268 p.
Keywords: Why has "America" - that is, the United States of America - become so much more than simply a place in the imagination of so many people around the world? In both Europe and Latin America, the United States has often been a site of multiple possible futures, a screen onto which could be projected utopian dreams and dystopian nightmares. Whether castigated as a threat to civilized order or championed as a promise of earthly paradise, America has invariably been treated as a cipher for modernity. It has functioned as an inescapable reference point for both European and Latin American societies, not only as a model of social and political organization - one to reject as much one to emulate - but also as the prime example of a society emerging from a dramatic diversity of cultural and social backgrounds.